2011
DOI: 10.1007/s13139-011-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Endoradiotherapy with Carrier-Added 4-[131I]Iodo-L-Phenylalanine: Clinical Proof-of-Principle in Refractory Glioma

Abstract: Systemic endoradiotherapy using up to 6.6 GBq of c.a.(131)I-IPA is not associated with clinically detectable toxicity. Measurable anti-tumour effects in gliomas were observed. (131)I-IPA warrants further evaluation as glioma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Therefore, we thought that para-211 At-PA uptake could be more specific to system L amino acid transporters. In addition, para-iodo-Lphenylalanine labelled with 123 I/ 131 I has been reported to show high uptake in glioma patients [7][8][9], suggesting the best coupling to be para-iodo/astato-L-phenylalanine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we thought that para-211 At-PA uptake could be more specific to system L amino acid transporters. In addition, para-iodo-Lphenylalanine labelled with 123 I/ 131 I has been reported to show high uptake in glioma patients [7][8][9], suggesting the best coupling to be para-iodo/astato-L-phenylalanine.…”
Section: Discussionmentioning
confidence: 99%
“…The derivative labelled with the gamma emitting isotope, para-123 I-iodo-L-phenylalanine ( 123 I-IPA), has been used with some success as a diagnostic imaging agent in glioblastoma patients [7]. The corresponding 131 I derivative ( 131 I-IPA) has been studied as a therapeutic agent, and is currently being advanced as a combination therapy with external beam radiation in a PhaseI/II clinical trial [8,9]. These PA-based compounds exhibit characteristics of high tumor to normal brain ratio that would be ideal for a targeted alpha therapeutic strategy.…”
Section: Research Papermentioning
confidence: 99%
“…In a human trial of systemic endo radio-therapy with [ 131 I]iodo-IPA (up to 6.6 GBq), patients did not present with acute or late radiotoxicity, neurotoxicity, and haematological or renal adverse events were not observed. This first-in-human investigation was performed in two patients with progressive gliomas, which were initially diagnosed as low-grade astrocytoma (WHO II) and oligodendroglioma (WHO II), respectively [240].…”
Section: Iodine-131mentioning
confidence: 99%
“…1 ) (Kratochwil et al 2014 ; Morita et al 2013 ; Hellwig et al 2008 ; Kersemans et al 2006 ). In addition, radiotherapy using β − -emitting radionuclide 131 I, para -[ 131 I]-iodo-L-phenylalanine ([ 131 I]-IPA) was also being investigated as a therapeutic agent and had shown efficacy in cancer treatment in clinical trials (Baum et al 2011 ). Recent reports have often suggested that radiolabeled compounds containing α-ray emitting radionuclides showed better therapeutic effects than those using β − -emitting radionuclides (McDevitt et al 2018 ; Morgenstern et al 2020 ; Sgouros et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%